Reviews (Reviews in religion and theology, 1999)
Books reviewed: Alice Laffey, The Pentateuch: A Liberation-Critical Reading O. Keel and C. Uehlinger, Gods, Goddesses and Images of God in Ancient Israel J. J. McDermott, What are They Saying About the Formation of Israel? M. E. Mills, Historical Israel: Biblical Israel – Studying Joshua to 2 Kings N. P. Lemche, The Israelites in Israel and Tradition Gerbern S. Oegema, The Anointed and His People: Messianic Expectations from the Maccabees to Bar Kochba M. Forward, Jesus: A Short Biography Jeffrey T. Tucker, Example Stories: Perspectives on Four Parables in the Gospel of Luke J. A. Darr, Herod the Fox: Audience Criticism and Lukan Characterization Alison Jasper, The Shining Garment of the Text: Gendered Readings of John's Prologue Helen C. Orchard,Courting Betrayal: Jesus as Victim in the Gospel of John Elisabeth Schüssler Fiorenza, Sharing Her Word: Feminist Biblical Interpretation in Context T. M. Shaw, The Burden of the Flesh: Fasting and Sexuality in Early Christianity Bernard McGinn, The Presence of God: A History of Western Christian Mysticism. Vol. 3, The Flowering of Mysticism: Men and Women in the New Mysticism 1200–1350 Kathleen Powers Erickson, At Eternity's Gate: The Spiritual Vision of Vincent van Gogh Charles E. Curran and Richard A. McCormick SJ (eds), John Paul II and Moral Theology E. J. Harris, What Buddhists Believe G. Studdert-Kennedy, Providence and the Raj: Imperial Mission and Missionary Imperialism Leon Roth, Is There a Jewish Philosophy? Rethinking Fundamentals Frank E. Eakin Jr., What Price Prejudice? Christian Antisemitism in America R. K. Wüstenberg, A Theology of Life: Dietrich Bonhoeffer's Religionless Christianity Douglas John Hall,Remembered Voices: Reclaiming the Legacy of ‘Neo-Orthodoxy’ T. Parfitt and E. Trevisan Semi (eds), The Beta Israel in Ethiopia and Israel: Studies on Ethiopian Jews C. Smith and J. Prokopy (eds), Latin American Religion in Motion K. B. Lyon & A. Smith, Jr. (eds), Tending the Flock: Congregations and Family Ministry Nantawan Boonprasat Lewis (ed.), Revolution of Spirit: Ecumenical Theology in Global Context John Macquarrie (ed. J. H. Morgan), On Being a Theologian: Reflections at Eighty